Abnormal kinetochore structure activates the spindle assembly checkpoint in budding yeast. - Pangilinan, F (1996)
Saccharomyces cerevisiae cells containing one or more abnormal kinetochores delay anaphase entry. The delay can be produced by using centromere DNA mutations present in single-copy or kinetochore protein mutations. This observation is strikingly similar to the preanaphase delay or arrest exhibited in animal cells that experience spontaneous or induced failures in bipolar attachment of one or more chromosomes and may reveal the existence of a conserved surveillance pathway that monitors the state of chromosome attachment to the spindle before anaphase. We find that three genes (MAD2, BUB1, and BUB2) that are required for the spindle assembly checkpoint in budding yeast (defined by antimicrotubule drug-induced arrest or delay) are also required in the establishment and/or maintenance of kinetochore-induced delays. This was tested in strains in which the delays were generated by limited function of a mutant kinetochore protein (ctf13-30) or by the presence of a single-copy centromere DNA mutation (CDEII delta 31). Whereas the MAD2 and BUB1 genes were absolutely required for delay, loss of BUB2 function resulted in a partial delay defect, and we suggest that BUB2 is required for delay maintenance. The inability of mad2-1 and bub1 delta mutants to execute kinetochore-induced delay is correlated with striking increases in chromosome missegregation, indicating that the delay does indeed have a role in chromosome transmission fidelity. Our results also indicated that the yeast RAD9 gene, necessary for DNA damage-induced arrest, had no role in the kinetochore-induced delays. We conclude that abnormal kinetochore structures induce preanaphase delay by activating the same functions that have defined the spindle assembly checkpoint in budding yeast.